Meaning in context: An analysis of Mahmoud Darwish's poetry / Ihmaid M. A. Ehmidat - Ihmaid M. A. , Ehmidat (2017)
The current study aimed to entrench the relationship between pronunciation and meaning using modern linguistics approach, by choosing Firth’s contextual theory of meaning or theory of context to be the means in the application process. The present study specifically aimed to identify the role of the contextual theory of meaning in determining the exact meanings of words contained in the poetic context as well as the eligibility of this theory in revealing the secrets and implications underlying these verses in Darwish’s poems. This emphasizes the significance of this research in revealing the great impact of applying the modern theories of linguistics for the reader, especially the application of the contextual theory to literary texts in highlighting the connotations and meanings of linguistic contexts. In addition, this research reveals the artistic methods and humorous rhetorical properties characterizing modern Arabic poetry, and what development and prosperity such poetry has gone through to keep pace with modern times. To ensure elegantin and advancement of the research towards excellences, the researcher used three scientific methods in carrying out this study: inductive approach which is based on an extrapolation of poetic texts, to find which is the most useful and beneficial to the research, descriptive analytical approach, which helps the researcher to analyze those literary texts in a literary and rhetorical manner to determine the relationships among the meaning, pronunciation and context, and the last approach is the contextual theoretical approach by following its way in dividing the linguistic contexts, rhetorically analyzing the selected texts in order to reveal the connotations and meanings of words. The findings of the study showed that the linguistic context has a significant impact and major role in directing the meanings and enriching the words with implications that fit the poetic context in which they are used for. Moreover, Mahmoud Darwish’s poetry is characterized by artistic features and rhetorical methods that expressed his thoughts and feelings in contexts compatible with the general meaning of the poem. According to the objectives of the study the results were divided into three groups, namely: vocal significance, towards: optimism, rhythm balance, and wonder and objection; syntactic and morphological significance, towards: maximization, regeneration, concealment, and exaggeration; and rhetorical significance, towards: disability and weakness, warning and alertness, and balance in meaning, and assertion. In conclusion, the researcher recommends the use of modern lingustics approaches and particulary the contextual approach in the process of analyzing literaty texts due to its capability in revealing the meanings and connotations in the linguistic context with extreme precision and infinite wisdom.